2022
DOI: 10.3389/fonc.2021.819817
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Membrane-Coated Nanoplatform for Targeted Tumor Immunotherapy

Abstract: Immunotherapy can effectively activate the immune system and reshape the tumor immune microenvironment, which has been an alternative method in cancer therapy besides surgery, radiotherapy, and chemotherapy. However, the current clinical outcomes are not satisfied due to the lack of targeting of the treatment with some unexpected damages to the human body. Recently, cell membrane-based bioinspired nanoparticles for tumor immunotherapy have attracted much attention because of their superior immune regulating, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For the activation of dendritic cells, cell membrane-coated NPs are helpful as an antigen and provoke humoral and T-cell immune reactions. 210 With the passage of time, various studies have concluded that nano-vaccines such as cancer-cell membrane- coated NPs similarly demonstrate promising anti-cancer ability. NPs cloaked using immune cell membranes can serve as vaccines in handling cancer, inflammation, bacterial infections and autoimmune infections.…”
Section: Immunotherapymentioning
confidence: 99%
“…For the activation of dendritic cells, cell membrane-coated NPs are helpful as an antigen and provoke humoral and T-cell immune reactions. 210 With the passage of time, various studies have concluded that nano-vaccines such as cancer-cell membrane- coated NPs similarly demonstrate promising anti-cancer ability. NPs cloaked using immune cell membranes can serve as vaccines in handling cancer, inflammation, bacterial infections and autoimmune infections.…”
Section: Immunotherapymentioning
confidence: 99%
“…Cancer immunotherapy has become a long-term solution for cancer treatment by inducing an antitumor immune response and lasting systemic protection. However, it also faces problems such as a low immune response rate, an inability to effectively predict immune efficacy, and insufficient targeting ability [ 117 ]. Various antigens are present on the surface of cancer cell membranes, which can act as tumor-specific antigens and be extracted by antigen presenting cells [ 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…This top‐down design approach wraps NPs with cellular membranes through simple physical methods, such as ultrasound or membrane extruders, imparting the NPs complex biological functions that originate from cell membranes, including the remarkable ability to interact with diverse cells and with the surrounding environment (Fang et al, 2018). Since Zhang et al reported the first cell membrane‐coating technology in 2011 (Hu et al, 2011), various membrane‐mimicking nanoplatforms based on different cells and NPs have been developed in biomedical applications, most of which are used in cancer therapy, including targeting the tumor microenvironment and cancer immunotherapy (Ai et al, 2018; Fang et al, 2018; Mu et al, 2021; Xiang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%